2015
DOI: 10.1007/s00256-015-2141-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ADC values in different malignancies of the skeletal musculature: a multicentric analysis

Abstract: Intramuscular malignant lesions had different ADC values on DWI. 22.8% of the tumors analyzed had low ADC values, 26.3% moderate, and 50.9% high ADC values. Muscle lymphoma had statistically significantly lower ADC values in comparison to muscle metastases and sarcomas. Muscle sarcomas presented with a broad range of ADC values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…DWI is an imaging modality sensitive to tissue alterations in several muscle disorders (Surov et al., ). For example, it has been shown that DWI correlates with cellularity in several tumors (Surov et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DWI is an imaging modality sensitive to tissue alterations in several muscle disorders (Surov et al., ). For example, it has been shown that DWI correlates with cellularity in several tumors (Surov et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that DWI correlates with cellularity in several tumors (Surov et al., ). Moreover, ADC values are significantly different between several muscle tumors reflecting various cellularity in muscle tumors (Surov & Behrmann, ; Surov et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, another study showed that there was no significant difference in ADC values between benign and malignant tumors [14]. Surov et al [15] reported that diffusion is determined by the balance between matrix and cellularity, but not the dignity of the lesion. Evaluation with diffusion-weighted MRI may be useful for differentiating chondroid lipoma from sarcoma.…”
Section: Discussionmentioning
confidence: 99%